Greenland, view of Kjerulf and Dicksons Fjords and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. In background on right L.A.B.'s Curry-comb Peak at junction of Left, Right, and Main Valleys. Its grooved side forms the west side of Left Valley. In the hollow at extreme background can be seen mountains which L.A.B. proves are those forming the eastern side of Hisinger Glacier [Hisinger Gletscher] after they turn S.W. Below these mountains, in the hollow, is Hisinger Glacer [Hisinger Gletscher] and the 'Unknown' Valley. In background on left, mountains forming left side of Kjerulfs [Kjerulf] Fjord and which -- upon reaching Hisinger Glacier [Hisinger Gletscher] at the Unknown Valley -- turn N.E. and form north side of Dickson [Dicksons] Fjord. In foreground - delta extending out from western shore. See 20-B-3 & 20-B-4 Photo taken from motor-boat going to inner end of Kjerulfs [Kjerulf] Fjord.